Flashcard as Media in Teaching English: A Systematic Literature Review - Sri Astuti; Noor Eka Chandra (Jurnal Sinestesia, 2023)
Media assist learners in gaining knowledge and skills. In this case the use of media is critical for providing students with knowledge of the lesson's subject. Using media for teaching is one solution an educator can make class's atmosphere more intriguing for students. Flashcards has been determined to be particularly effective among the current instructional method in teaching English skills. This literary study was carried out to check out flashcards's popularity in teaching English. This article use literature review method. This study is based on a systematic review of 30 journal articles in the databases Google Scholar, WoS (Web of Science), DOAJ (Directory Open Access Journal), and the website www.neliti.com (this website provided many journals in variation). This article discusses description of flashcards, advantages and disadvantages of flashcards, and the use of flashcards in teaching English. According to the findings of this literature review, flashcards are commonly used in teaching vocabulary rather than other language skills. The findings suggested that other variations in design and activities be used in the implementation of flashcards.